Energy transfer in supramolecular [Crypt-RE]-[W6I14] solids. Issue 28 (6th July 2020) - Hummel, Thorsten; Leis, Wolfgang; Eckhardt, Aaron; Ströbele, Markus; Enseling, David; Jüstel, Thomas; Meyer, Hans-Jürgen
Abstract : Photophysical properties of tungsten iodides with the [W6 I14 ] 2− cluster core have been described with respect to phosphorescence and phosphorescence quenching by molecular oxygen. Abstract : Photophysical properties of tungsten iodides with the [W6 I14 ] 2− cluster core have been described with respect to phosphorescence and phosphorescence quenching by molecular oxygen. This process involves energy transfer from excited triplet states of the cluster onto molecular oxygen. In the present study we investigate deactivation channels of exited triplet states of the [W6 I14 ] 2− cluster towards rare earth ions. For this purpose, we synthesized several supramolecular assemblies made of [W6 I14 ] 2− clusters and metal cryptates and investigated their crystal structures and photophysical properties. UV/Vis photoexcitation of solid [Crypt-A]-[W6 I14 ] (A = alkaline metal) and [Crypt-RE]-[W6 I14 ] revealed phosphorescence of the cluster, respectively of the photophysically active rare earth metal (RE) center. A cluster to cryptate energy transfer is proven with a photophysically active rare earth ion by the emission of Yb 3+ at 977 nm ( 2 F5/2 – 2 F7/2 ) and Nd 3+ 1072 nm ( 4 F3/2 – 4 I11/2 ). These results show that an effective excitation of near-infrared-emitting rare earth ions is possible under excitation up to 550 nm with [Crypt-RE]-[W6 I14 ] assemblies.